2006
DOI: 10.1073/pnas.0608344103
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and expression of chimeric POTE–actin genes in the human genome

Abstract: We previously described a primate-specific gene family, POTE, that is expressed in many cancers but in a limited number of normal organs. The 13 POTE genes are dispersed among eight different chromosomes and evolved by duplications and remodeling of the human genome from an ancestral gene, ANKRD26. Based on sequence similarity, the POTE gene family members can be divided into three groups. By genome database searches, we identified an actin retroposon insertion at the carboxyl terminus of one of the ancestral … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 43 publications
(49 citation statements)
references
References 21 publications
0
48
1
Order By: Relevance
“…The frozen tissue was ground in a mortar set and lysed with RIPA buffer (50 mM Tris-HCl, pH 7.5, 150 mM NaCl, 5 mM EDTA, 1% Nonidet P-40, 1% deoxycholate, 0.1% SDS, 1 mM PMSF, 1 mg/ml leupeptin, 1 mg/ml aprotinin). After sonication and centrifugation, 4 mg protein was immunoprecipitated by HP8 antibody and detected in Western blotting using PG5 MAb as previously described [4].…”
Section: Immunoprecipitation Western Blottingmentioning
confidence: 99%
See 1 more Smart Citation
“…The frozen tissue was ground in a mortar set and lysed with RIPA buffer (50 mM Tris-HCl, pH 7.5, 150 mM NaCl, 5 mM EDTA, 1% Nonidet P-40, 1% deoxycholate, 0.1% SDS, 1 mM PMSF, 1 mg/ml leupeptin, 1 mg/ml aprotinin). After sonication and centrifugation, 4 mg protein was immunoprecipitated by HP8 antibody and detected in Western blotting using PG5 MAb as previously described [4].…”
Section: Immunoprecipitation Western Blottingmentioning
confidence: 99%
“…The length of α helical region varies among paralogs and some paralogs do not contain this region. We have recently reported that several members of the POTE gene family contain an actin retroposon inserted at the carboxyl terminus of an ancestral POTE paralog in the process of gene evolution [4]. The POTE-2α and POTE-2γ actin fusion genes are expressed in embryonic stem cells and breast cancer cell lines [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…There are no obvious orthologs of POTE gene in other species; however, a distant ancestral gene has been identified in rodents [5]. Recently, we reported that there is an actin retroposon insertion at the carboxyl terminus of one of the ancestral POTE paralogs that occurred before the divergence of Old World monkeys and apes [6]. The resulting gene has duplicated and diverged into several POTE paralogs.…”
Section: Introductionmentioning
confidence: 99%
“…To determine the size of the POTE transcript expressed in hES cells, total RNA from the WA01 cell line was analyzed by northern blot hybridization using a probe 3Ј end of POTE transcript [6]. A specific band of about 7.5 kb in size was detected in WA01 lane, suggesting that the POTE transcript in this cell line is 7.5 kb in size (Fig.…”
Section: Expression Of Pote In Hes Cellsmentioning
confidence: 99%
See 1 more Smart Citation